High Fat Diet Enhances β-Site Cleavage of Amyloid Precursor Protein (APP) via Promoting β-Site APP Cleaving Enzyme 1/Adaptor Protein 2/Clathrin Complex Formation. - Masato Maesako; Maiko Uemura; Yoshitaka Tashiro; Kazuki Sasaki; Kiwamu Watanabe; Yasuha Noda; Karin Ueda; Megumi Asada-Utsugi; Masakazu Kubota; Katsuya Okawa; Masafumi Ihara; Shun Shimohama; et al. (PLoS ONE, 2015)
Obesity and type 2 diabetes are risk factors of Alzheimer's disease (AD). We reported that a high fat diet (HFD) promotes amyloid precursor protein (APP) cleavage by β-site APP cleaving enzyme 1 (BACE1) without increasing BACE1 levels in APP transgenic mice. However, the detailed mechanism had remained unclear. Here we demonstrate that HFD promotes BACE1/Adaptor protein-2 (AP-2)/clathrin complex formation by increasing AP-2 levels in APP transgenic mice. In Swedish APP overexpressing Chinese hamster ovary (CHO) cells as well as in SH-SY5Y cells, overexpression of AP-2 promoted the formation of BACE1/AP-2/clathrin complex, increasing the level of the soluble form of APP β (sAPPβ). On the other hand, mutant D495R BACE1, which inhibits formation of this trimeric complex, was shown to decrease the level of sAPPβ. Overexpression of AP-2 promoted the internalization of BACE1 from the cell surface, thus reducing the cell surface BACE1 level. As such, we concluded that HFD may induce the formation of the BACE1/AP-2/clathrin complex, which is followed by its transport of BACE1 from the cell surface to the intracellular compartments. These events might be associated with the enhancement of β-site cleavage of APP in APP transgenic mice. Here we present evidence that HFD, by regulation of subcellular trafficking of BACE1, promotes APP cleavage.